Implikasi Regulasi Tindak Pidana Illegal Logging Terhadap Kelestarian Lingkungan Hidup Ditinjau Dalam Perspektif Hukum Lingkungan - Milla Mudzalifah; Puti Priyana (Universitas Serang Raya, 2020)
Illegal logging is the activity of logging, transporting timber and selling timber which is a form of factual threat around borders that are illegal or do not have a permit from the authorities. These activities can cause environmental pollution and destruction which have a direct impact on environmental preservation. Illegal Logging in the substance of Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) is an act of a person that causes direct or indirect changes to the physical, chemical and biological characteristics of the environment so that it exceeds the standard criteria for environmental damage. Illegal logging practices that do not respect forest sustainability have resulted in invaluable destruction of forest resources. Even people's lives will also be directly affected, because state income is reduced by the loss of local biodiversity. This type of research uses normative legal research, the approach method used is the normative juridical approach with the aim of this research is to find out about how is the responsibility of criminal law in the field of illegal logging for environmental sustainability in the perspective of environmental criminal law. The result is that this act of illegal logging is punishable by imprisonment of at least 10 to 15 years, as well as an administrative sanction of Rp. 10-15 billion contained in article 78 of Law Number 41 Year 1999 concerning Forestry. Not only that, this illegal logging will also be more widely discussed if it is linked to forest encroachment which is also carried out illegally. These two activities can be described as Looting the Forest. Law on Environmental Management and Protection Number 32 Year 2009 hereinafter referred to as UUPPLH Number 32 Year 2009 has brought changes based on environmental management and protection in Indonesia. In the concept of criminal law, it explains the principle of ultimum remidium which is said to be the last resort for certain formal crimes. Keywords: Regulations; Environmental; Illegal; Log; Criminal;